Detection of acrosome in mouse sperm incubated in vitro using fluorescence staining technique - Abdullah, R.B.; Hasan Adli, Durriyyah Sharifah; Nooraain, H. (2006)
The protocol for detecting acrosome in mouse sperm was developed by using two types of fluorescent dyes namely fluorescein conjugated Pisum sativum agglutinin (FITC-PSA) and rhodamine conjugated Lens culinaris agglutinin (TRITC-LCA). The results showed that mean percentages of acrosome-intact sperm incubated in vitro were considerably low. After one-hour incubation there were 43.20±2.83, 31.81±8.44 and 30.90±4.15% for ICR, C57/6J and F1 sperm, respectively. Intact acrosome in ICR sperm was significantly reduced (P<0.05) to 16.95±4.23% after two-hour incubation, however, insignificant reduction (P>0.05) was found for C57/6J and F1 sperm, which were 30.03±2.06 and 20.93±3.81%, respectively. The results showed that both dyes FITC-PSA and TRITC-LCA suitably stained the mouse sperm and produced insignificant difference (P>0.05) in the percentages of acrosome-intact sperm, which were 40.03±4.20 and 49.79±4.63%, respectively. One-hour incubation was adequate to capacitate sperm in vitro. Low acrosome intact due to extended period of incubation and morphologically abnormal sperm could compromise in vitro fertilization rates.